2007
DOI: 10.1038/sj.leu.2404788
|View full text |Cite
|
Sign up to set email alerts
|

Deguelin inhibits expression of IκBα protein and induces apoptosis of B-CLL cells in vitro

Abstract: We investigated if deguelin, a naturally occurring rotenoid, was able to inhibit nuclear factor kappa B (NF-jB)-binding protein (IjBa) expression and to induce apoptosis in B-cell chronic lymphocytic leukemia (B-CLL) cells in vitro. Deguelin-induced cell death in the majority of B-CLL cells and was found to be more toxic toward B-CLL cells than to the normal mononuclear or B-cells, suggesting selectivity towards the malignant cells. Deguelin was found to reduce IjBa protein expression, and thus interacts with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 52 publications
3
16
0
Order By: Relevance
“…The results of fluorescence microscopic examination also revealed features characteristic of apoptosis, confirming the ability of deguelin to induce apoptosis in MPC-11 cells. Consistent with our results, other groups reported that deguelin induced apoptosis in various types of cells, including colon cancer, gastric cancer, leukemia, breast cancer and hepatic cancer cells (7,8,(17)(18)(19).…”
Section: Discussionsupporting
confidence: 92%
“…The results of fluorescence microscopic examination also revealed features characteristic of apoptosis, confirming the ability of deguelin to induce apoptosis in MPC-11 cells. Consistent with our results, other groups reported that deguelin induced apoptosis in various types of cells, including colon cancer, gastric cancer, leukemia, breast cancer and hepatic cancer cells (7,8,(17)(18)(19).…”
Section: Discussionsupporting
confidence: 92%
“…In this context, it is noteworthy that several other NF-B inhibitors have also shown promise in preclinical evaluation in primary CLL cells. 23,24, [43][44][45][46] The development of drug resistance is a major clinical problem in CLL. [47][48][49][50][51] Therefore, it is important to note that sensitivity to LC-1 was For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…It also increases the sensitivity of leukemia cells to chemotherapeutic agents (7) and suppresses the growth of human colon cancer cells (8). Deguelin blocks the proliferation of premalignant and malignant human bronchial epithelial (HBE) cells by inducing apoptosis (9).…”
Section: Introductionmentioning
confidence: 99%